Primaquine phosphate induces the apoptosis of ATRA‐resistant acute promyelocytic leukemia cells by inhibition of the NF‐κB pathway. Issue 4 (3rd March 2020) - Ma, Lan; Chen, Lianjuan; Li, Haoying; Ge, Lu; Wang, Siheng; Zhang, Zhida; Huang, He; Shi, Liuzhi; Li, Tong; Gu, Haihua; Lyu, Jianxin; He, Licai
Abstract: As a subtype of acute myeloid leukemia (AML), acute promyelocytic leukemia (APL) is characterized by a chromosomal translocation, most of which result in the production of a PML‐RAR alpha fusion protein. Although the overall survival rate of APL patients has improved dramatically due to all‐trans retinoic acid (ATRA) treatment, ATRA‐resistance remains a clinical challenge in the management of APL. Therefore, alternative agents should be considered for ATRA‐resistant APL patients. Here, we report that antimalaria drug primaquine phosphate (PRQ) exhibits an anti‐leukemia effect on both ATRA‐sensitive cell line NB4 and ATRA‐resistant APL cell lines, NB4‐LR2, NB4‐LR1, and NB4‐MR2. Moreover, PRQ significantly inhibited primary colony formation of untreated or relapsed APL patients. Further study showed that PRQ could induce the apoptosis of APL cells by inhibiting NF‐κB signaling pathway. The in vivo study showed that PRQ significantly inhibited NB4‐LR2 xenograft tumors growth. These results suggest that PRQ is a potential therapeutic agent for ATRA‐resistant APL patients. Abstract : PRQ induced the apoptosis of ATRA‐resistant APL cells by inhibiting NF‐κB signaling pathway in vitro and in vivo.